2019
DOI: 10.1371/journal.pone.0218089
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of in vivo MRI based cortical myelin mapping using T1w/T2w and R1 mapping at 3T

Abstract: In this manuscript, we compare two commonly used methods to perform cortical mapping based on myelination of the human neocortex. T1w/T2w and R1 maps with matched total acquisition times were obtained from a young cohort in randomized order and using a test–retest design. Both methodologies showed cortical myelin maps that enhanced similar anatomical features, namely primary sensory regions known to be myelin rich. T1w/T2w maps showed increased robustness to movement artifacts in comparison to R1 maps, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 48 publications
7
43
0
Order By: Relevance
“…Interestingly, we detected a similar offset between left and right hemispheric T 1 across acquisition sites, with higher values observed for the left hemisphere. This follows the inter-hemispheric differences with lower R 1 (i.e., higher T 1 ) values for the left hemisphere observed by Shams et al (2019), across different field strengths (Kim et al, 1994;Marques et al, 2017;Wansapura et al, 1999), and which could not solely be explained by the asymmetric B 1 + field. In fact, our results show that this difference intensifies after cleaning up remaining B 1 + residuals.…”
Section: Inter-site Cortical T 1 and Thickness Variabilitysupporting
confidence: 71%
“…Interestingly, we detected a similar offset between left and right hemispheric T 1 across acquisition sites, with higher values observed for the left hemisphere. This follows the inter-hemispheric differences with lower R 1 (i.e., higher T 1 ) values for the left hemisphere observed by Shams et al (2019), across different field strengths (Kim et al, 1994;Marques et al, 2017;Wansapura et al, 1999), and which could not solely be explained by the asymmetric B 1 + field. In fact, our results show that this difference intensifies after cleaning up remaining B 1 + residuals.…”
Section: Inter-site Cortical T 1 and Thickness Variabilitysupporting
confidence: 71%
“…To test this, we first extracted and compared average MRI T1w/T2w ratio values from each sulcus. The T1w/T2w ratio is a tissue contrast enhancement index that is correlated with myelin content (Figure 3a; (Glasser and Van Essen, 2011;Shams et al, 2019). We chose this index because myeloarchitecture is a classic criterion used to separate cortical areas from one another (Vogt and Vogt, 1919;Flechsig, 1920;Hopf, 1956;Dick et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In both cases, we found that coordinates for the centers of the M and P subdivisions in the majority of subjects were inconsistent with those obtained using the histological data (BigBrain), suggesting that these maps were not sufficient for parcellating the M and P subdivisions in the LGN. This most likely occurred because these values are prone to measurement biases (Shams et al, 2019). The unsuccessful parcellation of the M and P subdivisions using the PD weighted images or T1w/T2w maps indicated the advantage of acquiring MTV data for…”
Section: Inter-subject Variability and Hemispheric Differences In Mtvmentioning
confidence: 99%